Effects of addition of micro-scale TiB2 particles on microstructures and mechanical properties of S136 steel fabricated using directed energy deposition - Loy, Fai Onn (Nanyang Technological University, 2022)
Directed Energy Deposition (DED) is an Additive Manufacturing (AM) process in which focused thermal energy is used to fuse materials together by melting them as they are being deposited. In this project, S136 steel blocks, both with and without addition of micro-scale TiB2, were fabricated through DED, on which tensile and hardness tests were conducted, as well as observation of the microstructure through Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Electron Dispersive X-ray Spectrometer (EDS), and Electron Backscatter Diffraction (EBSD). Microstructural characterization results show that nano-scale particles enriched in Ti were distributed uniformly across the as-built TiB2-reinforced S136 blocks. The addition of TiB2 micro-scale particles to S136 steel led to increasing volume fractions of body-centered phase (BCC) structures, consisting of martensite and ferrite, along with a decrease in grain size. Mechanical test results reveal that both hardness and yield strength were increased when TiB2 was introduced, but ultimate tensile strength and ductility decreased. Fractography on fractured tensile samples demonstrates that both S136 and TiB2-reinforced S136 are brittle and show limited to no plastic deformation before failure.